Co-composting of food and green waste - Millaa-Armilla, Asli (Universiti Malaysia Sarawak (UNIMAS), 2007)
Co-composting of food and green waste in considered as the best alternative for enhancing seeds growth and germination. The composting materials obtained food waste (chicken, fish, vegetables, fruits and kitchen wastes) and green waste (shredded fresh leaves, barks and twigs). Compost is found environmental friendly and to be beneficial in enhancing and as a promoter to the seeds growth